Incomplete Endochondral Ossification of the Otic Capsule, A Variation in Children: Evaluation of Its Prevalence and Extent in Children with and without Sensorineural Hearing Loss - Sanverdi, S.E.; Ozgen, B.; Dolgun, A.; Sarac, S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Endochondral ossification of the otic capsule is a process that continues postnatally; hence, incomplete endochondral ossification is seen as pericochlear hypoattenuation on temporal bone CT scans of children. We determined the prevalence and extent of this entity in a large series and assessed its relation to age and underlying sensorineural hearing loss. MATERIALS AND METHODS: Initially, temporal bone CTs of 40 children with sensorineural hearing loss were retrospectively assessed and compared with those of a control group scanned for non-sensorineural hearing loss reasons to assess any difference in the prevalence or extent of incomplete endochondral ossification. Then the CT scans of 510 children (age range, 17 days to 17 years) were retrospectively reviewed, and any observed endochondral ossification areas were classified as mild, moderate, or extensive, according to their extent. RESULTS: Neither the presence nor degree of incomplete endochondral ossification had any significant correlation with the presence of sensorineural hearing loss (P = .08 and P = .1, respectively). Incomplete endochondral ossification was more frequently seen (62% of cases) than complete ossification. There was no statistically significant correlation between incomplete endochondral ossification and sex (P = .8), but an inverse correlation was found between the presence of incomplete endochondral ossification and increasing age (P < .001). Overall, mild incomplete endochondral ossification was the most frequent involvement pattern (44.4%). CONCLUSIONS: The pericochlear hypoattenuation in the otic capsule representing incomplete endochondral ossification is a normal finding in children and can be seen as a marked curvilinear hypoattenuation at younger ages in the absence of any clinical disorder. FAFfissula ante fenestramiEOincomplete endochondral ossificationOCotic capsuleSNHLsensorineural hearing loss